2020
DOI: 10.3390/sci2030063
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease (COVID-19): Handling Challenges in Kuwait

Abstract: The world is currently facing a serious pandemic of coronavirus disease 2019 (COVID-19) which started in Wuhan, China, and was then transmitted rapidly to other countries. Countries applied different methods and procedures in an attempt to prevent or reduce and/or control the incidence of cases and manage existing ones. This paper discusses the methods and procedures applied by Kuwait to control this epidemic, and how effective they have been. The State of Kuwait followed WHO, European CDC, US CDC, and/or othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…For instance, during the pandemic, they were asked to work (or continue working) in areas of high risks/exposures (e.g., as cleaners, domestic workers) without sufficient protections, and they were placed in unhygienic and cramped accommodations with inadequate medical facilities. Such multipronged adversities not only increased their chances of infection (some described such living areas as epicenters of COVID-19) but also triggered mental-health issues among the marginalized workers ( Gasana & Shehab, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, during the pandemic, they were asked to work (or continue working) in areas of high risks/exposures (e.g., as cleaners, domestic workers) without sufficient protections, and they were placed in unhygienic and cramped accommodations with inadequate medical facilities. Such multipronged adversities not only increased their chances of infection (some described such living areas as epicenters of COVID-19) but also triggered mental-health issues among the marginalized workers ( Gasana & Shehab, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, many migrant workers quarantined in unhygienic and cramped living spaces. Some news reports suggested that up to a dozen migrant workers were placed in a single room of dilapidated houses, where the availability of essential resources such as hand sanitizers, soaps, and sufficient water were scarce ( Gasana & Shehab, 2020 ; Kristiansen & Sheikh, 2014 ). Moreover, impossibilities in implementing social distancing and other measures (WHO recommended) and social habits of the migrants (influenced by collectivistic cultures) potentially made their living spaces epicenters of COVID-19 outbreak ( Karim et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported cases started to increase exponentially, which prompted the government to declare a ‘partial lockdown’ (referred to as ‘lockdown’ hereafter) beginning from 22 March until 10 May (50 days). Kuwait implemented gradual lockdown restrictions to help control the spread of SARS-CoV-2 [ 1 , 2 ], and all public and private transport, government and private sectors and non-essential industries were shut down during the ‘curfew’ hours of the lockdown. Private transport, although diminished significantly, was permitted only during the ‘non curfew’ hours.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the general secretary Xi Jinping stressed the importance of artificial intelligence to handle epidemic monitoring and analysis, resource allocation, prevention and treatment and virus tracing (People's Daily, 2020). Mental health illness in COVID-19 patients has been reported in various countries ( Begum et al, 2021 , Gasana and Shehab, 2020 ).…”
Section: Discussionmentioning
confidence: 99%